The Continuance Usage Of Physical Activity Tracking Technology With Social Media: Connecting The Dots For Singapore - Wanichavorapong, Nittee; Razak Che Hussin, Ab; Fadhil Yusof, Ahmad; Mohamed Dahlan, Halina (International Journal of Engineering and Technology, 2018)
Physical activity (PA) tracking technology can assist individual in monitoring physical activities in eHealth while gaining popularity and enjoying a flourishing market. Social media (SM) offers huge advantages to PA tracking technology (PATT). Yet, the continuance usage is the cornerstone of IT goods and services; otherwise failed. The limited knowledge of IS continuance in PATT-SM is the motive. Our purpose is to analyze the factors that drive users to continue using PATT-SM. This study demonstrated the use of expectation confirmation model (ECM) and value factors to predict CI in a variety of perspectives including social, economics, behavior, and cognitive. Through data collection, a survey method was conducted in Singapore (n=201). The proposed model has been assessed for reliability and validity. The PLS-SEM method was used to investigate the cause-effect relationship between the constructs in a multi-linear regression style. The results exhibited that the all constructs of ECM constructs had a statistically significant impact on continuance intention (CI); in addition, usefulness has an impact on CI. However, perceived influence had rather a negative impact on CI. Social value received no significant association with CI. Then, network size and complementarity had also positive and statistical significance on perceived influence whereas complementarity yielded less impact.Â